Paroxysmal non-kinesigenic dyskinesia is caused by mutations of the MR-1 mitochondrial targeting sequence - Ghezzi, Daniele; Viscomi, Carlo; Ferlini, Alessandra; Gualandi, Francesca; Mereghetti, Paolo; DeGrandis, Domenico; Zeviani, Massimo (Human molecular genetics, 2009)
Paroxysmal non-kinesigenic dyskinesia (PNKD) is an autosomal-dominant movement disorder characterized by attacks of dystonia, chorea and athetosis. Myofibrillogenesis regulator-1 (MR-1), the gene responsible for PNKD, is transcribed into three alternatively spliced forms: long (MR-1L), medium (MR-1M) and small (MR-1S). Two mutations, A7V and A9V, were previously discovered in the N-terminal region common to MR-1L and MR-1S. We now found a third mutation, A33P, in a new PNKD patient in the same region. Contrary to previous reports, we show here that the mutation-free MR-1M is localized in the Golgi apparatus, ER and plasma membrane, whereas both MR-1L and MR-1S isoforms are mitochondrial proteins, imported into the organelle thanks to a 39 amino acid-long, N-terminal mitochondrial targeting sequence (MTS). The MTS, which contains all three PNKD mutations, is then cleaved off the mature proteins before their insertion in the inner mitochondrial membrane. Therefore, mature MR-1S and MR-1L of PNKD patients are identical to those of normal subjects. We found no difference in import efficiency and protein maturation between wild-type and mutant MR-1 variants. These results indicate that PNKD is due to a novel disease mechanism based on a deleterious action of the MTS.